2010
DOI: 10.5172/conu.2010.34.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and optimism in rural youth: Gender differences

Abstract: Both instruments' mean scores were in the range of average for this population, with females scoring lower than males in both self-esteem (p < 0.0001) and optimism (p < 0.0001). The results of this study have nursing implications for evidenced based interventions that target self-esteem and optimism. Attention to self-esteem and optimism in female youth is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
2
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 26 publications
4
37
2
9
Order By: Relevance
“…Sin embargo, el tamaño del efecto obtenido es muy reducido (δ=.11; Macbeth et al, 2011), lo que podría indicar que realmente las diferencias se deben al amplio tamaño muestral y no a diferencias inherentes a la propia variable en ambos sexos. Como muestran trabajos precedentes, existe una cierta inconsistencia en cuanto a las diferencias en función del sexo (Eloranta et al, 2012;Plagnol y Easterlin, 2008;Puskar et al, 2010). En opinión de autores como Tusaie y Patterson (2006), aunque en general los adolescentes no perciben la posibilidad de sufrir eventos negativos, parece que las mujeres se consideran más vulnerables ante los diferentes eventos estresantes, causando esto un nivel de optimismo ligeramente inferior respecto a los hombres.…”
Section: Discusión Y Conclusionesunclassified
“…Sin embargo, el tamaño del efecto obtenido es muy reducido (δ=.11; Macbeth et al, 2011), lo que podría indicar que realmente las diferencias se deben al amplio tamaño muestral y no a diferencias inherentes a la propia variable en ambos sexos. Como muestran trabajos precedentes, existe una cierta inconsistencia en cuanto a las diferencias en función del sexo (Eloranta et al, 2012;Plagnol y Easterlin, 2008;Puskar et al, 2010). En opinión de autores como Tusaie y Patterson (2006), aunque en general los adolescentes no perciben la posibilidad de sufrir eventos negativos, parece que las mujeres se consideran más vulnerables ante los diferentes eventos estresantes, causando esto un nivel de optimismo ligeramente inferior respecto a los hombres.…”
Section: Discusión Y Conclusionesunclassified
“…Optimism has been described as a general tendency to expect a positive outcome even in the face of obstacles or when bad things happen (Scheier & Carver, 1985;Scheier & Carver, 1987). Optimism is indicated to have a positive affect on physical and psychosocial well-being, such as: Depressive symptomology, the impact of stress, self esteem, forming and maintaining relationships, choice of coping strategies, adjustment to university life, scholastic competence, and perception of support (Aspinwall & Taylor, 1992;Fass & Tubman, 2002;Ferguson & Goodwin, 2010;Hatchett & Park, 2004;Krypel & Henderson-King, 2010;Nes & Segerstron, 2006;Puskar et al, 2010).…”
Section: Transition To Universitymentioning
confidence: 99%
“…Literature has highlighted the benefits that optimism have on physical and psychosocial wellbeing, i. e. reducing depressive symptoms and stress impact, enhancing self-esteem, forming and maintaining relationships, and favoring adjustment to university life (Ferguson & Goodwin, 2010;Hatchett & Park, 2004;Krypel & Henderson-King, 2010;Puskar et al, 2010). In a recent study, it was found that optimistic students were more academically engage that non-optimistic ones (Ouweneel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%